Two principles for the next round, or, How to bring developing countries in from the cold - Stiglitz, Joseph E. ([s.n.] GenevaCH, 1999)
Looks at the costs and benefits of trade libealization from a general pespective as well as from the perspective of a developing country. Focuses on two basic principles that should govern the next set of trade negotiations: fairness, and, especially fairness to the developing countries and comprehensiveness.